The association between type of trauma, level of exposure and addiction. (July 2021) - Levin, Yafit; Lev Bar-Or, Ruth; Forer, Reni; Vaserman, Magali; Kor, Ariel; Lev-Ran, Shaul
Highlights: There is a strong association between all types of trauma and specific substances and behaviors. Secondary ("indirect") exposure is highly associated with addiction. In combat-related trauma, rates of behavioral addictions are higher among those with secondary exposure. Abstract: Exposure to trauma is considered a risk factor for the development of addictive disorders. Currently, there is a knowledge gap concerning specific links between types and levels of exposure to traumatic events and addiction. In this study we explored the associations between interpersonal trauma and risk of addictive behaviors, stratified by type of trauma (physical, weapon, sexual assault, and combat) and level of exposure (direct/indirect), focusing on a wide range of substances and behaviors. Data from an online representative sample of 4025 respondents were collected, including the Life Events Checklist (LEC-5), substance use disorders and behavioral addictions metrics, and sociodemographic data. Substantial differences were found between specific types of trauma and risk of addiction. Among those exposed to sexual assault, the risk of alcohol use disorder was found to 15.4%, 95%CI[14.4–16.4%], compared to 12.1%, 95%CI[11.3–12.8] among those exposed to combat-related trauma. Both direct and indirect exposure to trauma were found to be significantly related with risk of addiction. While direct exposure was most highly associated with addictions across several types of trauma, in the case of combat-related trauma, indirect exposure was more highly associated with alcohol and pornography addiction (14.5%, 95%CI[13.2–15.8%] and 10.0%, 95%CI[6.3–15.0%], respectively) compared to direct exposure (10.7%, 95%CI[9.9–11.6%] and 7.4%, 95%CI[4.7–11.6%], respectively). Our findings emphasize the strong association between all types of trauma and the risk of several specific substance and behavioral addictions. Specifically, the role of indirect exposure to trauma is highlighted.